2005
DOI: 10.1063/1.2130392
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic observations of condensation of water on lotus leaves

Abstract: We report an in situ observation of water condensation and evaporation on lotus leaf surfaces inside an environmental scanning electron microscope. The real-time observation shows, at the micrometer length scale, how water drops grow to large contact angles during water condensation, and decrease in size and contact angle during the evaporation phase of the experiment. To rationalize the observations, we propose a geometric model for liquid drops on rough surfaces when the size of the drop and surface roughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
129
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(138 citation statements)
references
References 23 publications
7
129
1
1
Order By: Relevance
“…In contrast, and although this process is of major importance for the evaluation of corrosion, the studies of condensation-induced wetting on superhydrophobic surface and their corresponding wetting properties (self-cleanliness, different wetting states), are much less documented [18][19][20][21][22][23][24][25][26][27][28][29]. The aim of the present work is thus to study condensation of water on a multiscale rough superhydrophobic surface where the contact angle is varied in a wide range (70-150 • ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, and although this process is of major importance for the evaluation of corrosion, the studies of condensation-induced wetting on superhydrophobic surface and their corresponding wetting properties (self-cleanliness, different wetting states), are much less documented [18][19][20][21][22][23][24][25][26][27][28][29]. The aim of the present work is thus to study condensation of water on a multiscale rough superhydrophobic surface where the contact angle is varied in a wide range (70-150 • ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from traditional superhydrophobic surfaces, which are characterized by the bouncing or rolling off of deposited millimeter-size large drops, [32,33] CMDSP surfaces support the self-removal capability of smallscale condensate microdrops. It has been reported that classical superhydrophobic lotus leaves (Figure 1a), [34][35][36][37] as well as artificial surfaces consisting of hierarchical micro-and nanostructures, [38] one-tier microstructures, [39][40][41][42][43] or nanostructures [44,45] with larger characteristic interspaces, present a low-adhesivity property to the deposited water macrodrops, but become highly adhesive to condensed microdrops (Figure 1b). This is because moisture easily penetrates the microscale valleys or cavities.…”
mentioning
confidence: 99%
“…The reason for the formation of SiO 2 beads at even spacing on the string is that the beads may not reach the critical size and weight, which allow them to slide down along the boron string to form a super SiO 2 bead at the root of each belt, just like the water droplets behave on the lotus leaves. 8 The microstructure of the as-synthesized boron-SiO 2 necklacelike structures is also revealed in Fig. 4.…”
mentioning
confidence: 99%